Structures of feeling in seventeenth-century cultural expression - McClary, Susan (UCLA Clark Memorial Library series, 2013)
Structures of Feeling in Seventeenth-Century Cultural Expression explores how artists made use of various cultural forms -- notably the visual arts, poetry, theatre, music, and dance -- to grapple with human values in the increasingly heterodox world of the 1600s.